Scientific and Research Review of Eloquence of Quran e Hakeem: قرآن حکیم کی فصاحت وبلاغت کاعلمی وتحقیقی جائزہ - Zahidi Balyalvi, Mufti Zaheer Abbas (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
The Holy Quran which was revealed in Arabic language, it’s verses have been explained with help of Ahadith and Aasar as well as Quran itself. The Holy Quran‘s basic understanding is based on comprehension of Arabic language. The eloquence of the Holy Quran is a great miracle. Which has dazzled the people of the language and this understanding is a key to the Holy Quran that is why this title has been designed for research. The Arabs possessed a remarkable memory and were an eloquent people. Their eloquence and memory found expression in their poetry and literature. It is no small wonder that Allah choose the Arabic language for his final dispensation and preservation of his word. The Arabs were impressed by the eloquence of Holy Quran. The eloquence of the Holy Quran dazzled the Arabs poets and it’s litterateur. Verse 90 of Surah An-Nahl is one of the verses therefore astonished the Arabs with its eloquence. This verse is a perfect example of eloquence. its words are short and meanings are wide. After that Walid bin Mughira was convinced and believed that thase are wat words and Usman bin Mazoon said: The eloquence of this verse gave me light of faith, verse 90 of surah an-nahl also guides us to eradicate all social evils and create an ideal society.